2021
DOI: 10.3390/jof7090784
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium musae from Diseased Bananas and Human Patients: Susceptibility to Fungicides Used in Clinical and Agricultural Settings

Abstract: Fusarium musae belongs to the Fusarium fujikuroi species complex. It causes crown rot disease in banana but also keratitis and skin infections as well as systemic infections in immunocompromised patients. Antifungal treatments in clinical and agricultural settings rely mostly on molecules belonging to the azole class. Given the potential risk of pathogen spread from food to clinical settings, the goal of the work was to define the level of susceptibility to different azoles of a worldwide population of F. musa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…This study, analysing the mitochondrial genomes of 18 F. musae strains, confirms previous observations based on nuclear genes (TEF and RPB2) [5,7], which showed that F. musae strains from banana and human patients are interspersed in the species tree. This indirectly confirms the ability of F. musae to cross-infect distant hosts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study, analysing the mitochondrial genomes of 18 F. musae strains, confirms previous observations based on nuclear genes (TEF and RPB2) [5,7], which showed that F. musae strains from banana and human patients are interspersed in the species tree. This indirectly confirms the ability of F. musae to cross-infect distant hosts.…”
Section: Discussionsupporting
confidence: 90%
“…Based on multilocus sequence typing, F. musae can be distinguished from its sister species F. verticillioides [2]. The two species show a diverse susceptibility to azoles, with F. musae having a higher tolerance to some fungicides compared to F. verticillioides [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these isolates exhibit resistance to multiple antifungals [ 21 ] mainly associated with cyp51A TR34/L98H or TR46/Y121F/T289A mutations [ 22 , 23 ] and, rather concerningly, they are now spreading globally [ 24 ]. A similar trend of reduced azole susceptibility in isolates of the Fusarium solani [ 25 ] and Fusarium fujikuroi [ 26 ] species complexes of agriculture and human origin has been recently reported.…”
Section: Introductionsupporting
confidence: 70%
“…However, it is affected by several postharvest fungal diseases, including crown rot (CR) (González‐Jiménez et al., 2023; Kulkarni et al., 2021), anthracnose (Vilaplana, Hurtado, & Valencia‐Chamorro, 2018; Vilaplana, Pazmiño, & Valencia‐Chamorro, 2018) and cigar rot (Youssef et al., 2020), with CR being the most economically important disease (Kamel et al., 2016; Krauss & Johanson, 2000; Lassois et al., 2011; Yahan et al., 2019). CR is caused by a fungal complex, Colletotrichum musae (Cm), Lasiodiplodia theobromae (Kulkarni et al., 2021) and Fusarium musae (Tava et al., 2021). The control of decay is carried out mainly with conventional synthetic chemical fungicides such as prochloraz, imazalil and thiabendazole (TBZ); however, the prolonged use of these fungicides has various negative effects such as environmental contamination, residue accumulation in the fruit above permissible levels and the appearance of fungal strains resistant to fungicides (Gatto et al., 2011; Jinasena et al., 2011; Mari et al., 2003).…”
Section: Introductionmentioning
confidence: 99%